2014
DOI: 10.1016/j.mito.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of PINK1 for increased PGC-1α-mediated mitochondrial fatty acid oxidation and their associations with Alzheimer disease and diabetes

Abstract: Down-regulation of PINK1 and PGC-1α proteins is implicated in both mitochondrial dysfunction and oxidative stress potentially linking metabolic abnormality and neurodegeneration. Here, we report that PGC-1α and PINK1 expression is markedly decreased in Alzheimer disease (AD) and diabetic brains. We observed a significant down-regulation of PGC-1α and PINK1 protein expression in H2O2-treated cells but not in those cells treated with N-acetyl cysteine. The protein levels of two key enzymes of the mitochondrial β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Disruption of this process leads to bioenergetic failure and intracellular lipid accumulation. This ectopic fatty acid accumulation further inhibits mitochondrial function, leading to increased oxidative stress and apoptotic neuronal cell death in diabetes [39, 40]. Additionally, elevated levels of ketone bodies (acetoacetate, 3-hydroxybutyrate and acetone) in our study suggest that present of transformation of energy metabolism substrate.…”
Section: Discussionmentioning
confidence: 66%
“…Disruption of this process leads to bioenergetic failure and intracellular lipid accumulation. This ectopic fatty acid accumulation further inhibits mitochondrial function, leading to increased oxidative stress and apoptotic neuronal cell death in diabetes [39, 40]. Additionally, elevated levels of ketone bodies (acetoacetate, 3-hydroxybutyrate and acetone) in our study suggest that present of transformation of energy metabolism substrate.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, some reports found alterations in FAO in neurodegenerative disorders and also neuroprotective effects associated to the activation of FAO, which suggest that Nrf2-induced FAO can be a potential therapeutic target. For example, it was shown that the levels of two of the main enzymes for β-oxidation, acyl-coenzyme A dehydrogenase and mitochondrial trifunctional enzyme subunit α are reduced in AD patients (Choi et al, 2014). In a different study, 3-hydroxyacylCoA dehydrogenase, which catalyzes the oxidation of 3-hydroxyacyl-CoAs in the mitochondrial FAO, was shown to protect against the MPTP-induced impairment of oxidative phosphorylation and ATP production in this model of PD (Tieu et al, 2004).…”
Section: Nrf2 and Lipid Metabolismmentioning
confidence: 87%
“…Prevention of mitochondrial dysfunction is thought to be the main therapeutic strategy for the delay in progression of neurodegenerative disorders, including Alzheimer's, Parkinson's, and prion disease . Recent studies have shown that the melatonin‐mediated autophagy activation prevents prion‐mediated neurotoxicity via protection of mitochondrial function .…”
Section: Discussionmentioning
confidence: 99%